KECERDASAN EMOSIONAL DAN PERILAKU MANUSIA (DALAM PERSPEKTIF ANTROPOLOGI) LUH SURYATNI - LUH SURYATNI (JURNAL MITRA MANAJEMEN, 2015)
ABSTRACTEmotional intelligence greatly affects human behavior since human being can expressthemselves with their emotion. Emotions can also help human to form their owncharacter. In which, later on will produce the behavior that impossible to differentiate fromthe influence of environment, genetic, and experience. Just try to imagine what wouldhappen if human beings do not have emotions? It is certainly not just the same as living.It is not enough to prepare you for facing the turmoil brought by the difficulties of life.Ample of evidences show that people who are emotionally capable, can understand anddeal with their own feelings. They also tend to be able to read and deal with the feelingsof others effectively, which is a great advantage to have in every area of life. People whohave good emotional intelligence (stable) are able to resolve the issue with a clear mindbecause their logic/reasoning is not affected by their unstable emotion. Thus, they willmore likely to be succeed in life. So, it is clear that emotional intelligence is a greatinfluence for human behavior because through the stability of their emotional intelligence,people can avoid themselves from the behavior that will affect poorly whether tothemselves or their surrounding environment.Keyword : Emotional intelligence and behavior